Binding of microRNAs with mRNAs of Growth Regulating Transcription Factors Genes in Arabidopsis, Rice and Maize (Experimental biology, 2015)
The interaction of microRNAs with mRNAs of growth regulating transcription factors in arabidopsis, rice and corn is studied. It was found that among 338 miRNAs in arabidopsis only ath-miR396 family efficiently bound to GRFmRNAs. It was revealed that among 661 rice miRNAs all nine members of osa-miR396 family bound to mRNAs of nine growth regulatory factors with high specificity. It was found that all eight members of zma-miR396 family out of 321 corn miRNAs bound to 36 mRNAs of growth regulating factors with high specificity
Keywords: miRNA; mRNA; miR396; plant